Leaf-based induction of protocorm-like bodies, their encapsulation, storage and post-storage germination with genetic fidelity in Mokara Sayan×Ascocenda Wangsa gold - Gantait, Saikat; Subrahmanyeswari, Tsama; Sinniah, Uma Rani (Elsevier, 2022)
An innovative and accelerated in vitro mass propagation protocol via direct induction of protocorm-like bodies (PLBs) from leaf sections of orchid hybrid Mokara Sayan × Ascocenda Wangsa gold was developed for the first time. Initially, leaf sections were transferred into Murashige and Skoog (MS) medium supplemented with two cytokinin sources namely, thidiazuron (TDZ) and zeatin with variable concentrations. The earliest (∼8 days) induction of PLBs with maximum number (34 PLBs cm–2 leaf section) and induction frequency (82.8 %) were recorded in MS medium fortified with 3 mg L–1 TDZ. The same medium formulation resulted in the highest growth rate (∼93.7 mg day–1) with maximum diameter of PLBs (3.4 mm) when compared with other treatments. Observations on proliferating PLBs under variable pressure scanning electron microscopy illustrated their distinctive growth phases wherein proliferating PLBs exhibited globular shape, typical epidermal texture with a rough surface that steadily became more wrinkled, consisting of basal absorbing hair-bodies and the apical zone forming shoot primordia. Stereo microscopic observations revealed gradual maturation of PLBs, initiation of leaf and shoot primordia. PLBs were encapsulated with calcium-alginate for short-term storage and germplasm exchange. Lower concentrations of sodium alginate (1 and 2 %) produced synthetic seeds that were soft to grip and extremely irregular in shape, whereas higher concentration (4 %) resulted in stiffness of synthetic seeds and reduced germination frequency. The most suitable gel matrix to form uniform spherical beads was optimized at 3 % sodium alginate and 75 mM calcium chloride. Synthetic seeds were effectively stored at 25 °C for up to 180 days. The germination efficiency of synthetic seeds gradually declined after storage at both 4 °C and 25 °C, with synthetic seeds stored at 25 °C being more tolerant than those stored at 4 °C. Even after 180 days of storage, the synthetic seeds that were stored at 25 °C exhibited 71.2 % germination frequency and ∼14 days to germination. Synthetic seeds stored at 4 °C deteriorated rapidly and degenerated completely within 180 days. Random amplified polymorphic DNA marker-based analysis carried out with randomly selected synthetic seed-derived plantlets showed 100 % monomorphism with a total 512 bands of molecular size ranging between 130—2100 bp, ensuring post-storage genetic fidelity.